Предмет:
МатематикаАвтор:
анонимРешим уравнение (2 * a + 5 * b - 3 * c) * 14 = 0;
14 * (2 * a + 5 * b - 3 * c) = 0;
2 * a + 5 * b - 3 * c = 0;
1) Выразим переменную а и получим:
2 * a + 5 * b - 3 * c = 0;
2 * a = -5 * b + 3 * c;
2 * a = 3 * c - 5 * b;
a = (3 * c - 5 * b)/2;
2) Выразим переменную b и получим:
2 * a + 5 * b - 3 * c = 0;
5 * b = -2 * a + 3 * c;
5 * b = 3 * c - 2 * a;
b = (3 * c - 2 * a)/5;
3) Выразим переменную c и получим:
2 * a + 5 * b - 3 * c = 0;
-3 * c = -2 * a - 5 * b;
3 * c = 2 * a + 5 * b;
c = (2 * a + 5 * b)/3.
Автор:
heathae9kДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
ИнформатикаАвтор:
анонимОтветов:
Смотреть